2011
DOI: 10.1097/bor.0b013e32833ee946
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ and IL-17: the two faces of T-cell pathology in giant cell arteritis

Abstract: Purpose of review Granuloma formation in giant cell arteritis (GCA) emphasizes the role of the adaptive immunity and highlights the role of antigen-specific T cells. Recent data demonstrate that at least two separate lineages of CD4 T-cells participate in vascular inflammation, providing an important clue that multiple disease instigators may initiate pathogenic immunity. Recent finding IFN-γ-producing Th1 cells and IL-17-producing Th17 cells have been implicated in GCA. Patients with biopsy-positive GCA und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 35 publications
2
84
1
3
Order By: Relevance
“…Recent data suggest that changes in the composition of the T-cell infiltrate allow the distinction of the arteritis into early and late GCA [75,76]. Th1 cells and Th17 cells seem in fact to predominate in early phases of GCA [76]. Interestingly, a stronger IL-17A expression in GCA patients has been demonstrated to be associated with less relapses, also requiring significantly shorter treatment periods [79].…”
Section: Cd4 + T Cells Play Central Roles In the Function Of The Immumentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data suggest that changes in the composition of the T-cell infiltrate allow the distinction of the arteritis into early and late GCA [75,76]. Th1 cells and Th17 cells seem in fact to predominate in early phases of GCA [76]. Interestingly, a stronger IL-17A expression in GCA patients has been demonstrated to be associated with less relapses, also requiring significantly shorter treatment periods [79].…”
Section: Cd4 + T Cells Play Central Roles In the Function Of The Immumentioning
confidence: 99%
“…The receptor for IL-9 activates endothelial cells, induces the expression of mast cell proteases and activates neutrophils [77]. Recent data suggest that changes in the composition of the T-cell infiltrate allow the distinction of the arteritis into early and late GCA [75,76]. Th1 cells and Th17 cells seem in fact to predominate in early phases of GCA [76].…”
Section: Cd4 + T Cells Play Central Roles In the Function Of The Immumentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, lupus-prone MRL-lpr/lpr mice receiving low doses of G-CSF showed an increased glomerular deposition of immunoglobulins and exacerbated lupus disease (8). The implicated Th17 T cells and the increased IL-17 production are together considered to contribute to the pathogenesis of GCA (2). It has been reported that activated neutrophils can also produce IL-17 (9).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of dendritic cells (DC) caused by microorganisms has been suggested to play a role in the pathogenesis of GCA (1). T helper 1 (Th1)-inducing signals and interleukin 17 (IL-17) have also been reported to be involved in this condition (2). However, the precise mechanism remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%